REGULATING FOOD WASTE MANAGEMENT IN INDONESIA: DO WE NEED AN OMNIBUS LAW (AGAIN)? - Satyawati, Ni Gusti Ayu Dyah; Suyatna, I Nyoman; Gede Arya Sumerta Yasa, Putu; Palguna, I Dewa Gede; Rajaratnam, Nadeeka (UI Scholars Hub, 2024)
Indonesia was regarded to be the world's second-largest food loss and waste-producing country. Food waste contributes the most significant amount in Indonesia compared to other types of waste. This paper aims to discuss three legal issues. First, it identifies, in descriptive-normative means, the legal framework regulating food waste, which is the intersection of two legal regimes: 'the food management' and 'the waste and environmental management”. Second, it presents a comparative study by exploring the more advanced food waste legal frameworks, which take examples from Europe. The third objective is to recommend legal, institutional, and policy steps to mainstream food waste management in Indonesia. This paper suggests that statutory regulations have indicated an initial concern about food waste; however, they do not provide a strict mandatory obligation to relevant stakeholders. Indonesia may use Europe’s remarkable achievements as lessons learned in initiating a comprehensive legal framework for food waste in the future. This paper, therefore, proposes a Law on Sustainable Food System as an ius constituendum to figure out a comprehensive solution for combining food management and environmental sustainability needs. In terms of legislative drafting, an omnibus law seemed suitable for drafting such a law, which crosses different legal regimes, and the existing provisions are spread in various regulations.